2013
DOI: 10.1242/jcs.125799
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mitochondrial-nuclear redistribution of the immunophilin FKBP51 is regulated by PKA signaling pathway to control gene expression in the process of adipocyte differentiation

Abstract: Glucocorticoids play an important role in adipogenesis through the glucocorticoid receptor (GR) that forms a heterocomplex with Hsp90•Hsp70 and one high molecular weight immunophilin, either FKBP51 or FKBP52. When 3T3-L1 preadipocytes are induced to differentiate, FKBP51 expression progressively increases, whereas FKBP52 decreases, and Hsp90, Hsp70, p23 and Cyp40 remain unchanged. Interestingly, FKBP51 rapidly translocates from mitochondria to the nucleus where it is retained upon its interaction with chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 69 publications
4
79
2
1
Order By: Relevance
“…20 Then, we assessed FKBP51, FKBP52, PR, and GR expression. Immunoblotting indicated that, as reported in other cell types, 32,33 FKBP51 is present in the nucleus and cytoplasm of cultured DCs and that glucocorticoid pays a dominant role in reciprocally up-regulating FKBP51 and down-regulating GR expression. By comparison with FKBP51, PR expression displayed dominant progestin-mediated down-regulation.…”
Section: Role Of Fkbp51 In Inducing Functional P4 Withdrawal During Lsupporting
confidence: 71%
“…20 Then, we assessed FKBP51, FKBP52, PR, and GR expression. Immunoblotting indicated that, as reported in other cell types, 32,33 FKBP51 is present in the nucleus and cytoplasm of cultured DCs and that glucocorticoid pays a dominant role in reciprocally up-regulating FKBP51 and down-regulating GR expression. By comparison with FKBP51, PR expression displayed dominant progestin-mediated down-regulation.…”
Section: Role Of Fkbp51 In Inducing Functional P4 Withdrawal During Lsupporting
confidence: 71%
“…38 In regard to adipogenesis, we have recently shown that no change is observed in the protein expression level of Hsp90 during the differentiation of 3T3-L1 preadipocytes. 39 It remains to be explored whether there are differences in the expression of the different Hsp90s during adipogenesis and whether they are deregulated in obesity due to the functional importance of this chaperone in response to cell stress.…”
Section: Hsp90 Participates In the Control Of Pparγmentioning
confidence: 99%
“…FKBP51 expression progressively increases whereas FKBP52 decreases as adipogenesis proceeds. 39,60 The differences observed between these studies may possibly depend on the development of highly sensitive and specific antibodies now available for the study of these IMMs. Importantly, the changes in level of expression of both IMMs during 3T3-L1 preadipocyte differentiation are in agreement with the high expression of FKBP51 and low levels of FKBP52 in white adipose tissue (J.T.…”
Section: High Molecular Weight Immunophilins In Adipocyte Differentiamentioning
confidence: 99%
See 1 more Smart Citation
“…This fact is shown in the model of Figure 2-A. It should be noted that FKBP51 was not recovered, associated to cytoplasmic structures of the NPC, although very recent evidence demonstrated that FKBP51 is able to interact with lamin B in the inner face of the nuclear envelope [94,95].…”
Section: The Hsp90-based Heterocomplex Interacts With the Nuclear Porementioning
confidence: 94%